A biologically inspired QoS routing algorithm for mobile ad hoc networks. (10th May 2010) - Liu, Z.; Kwiatkowska, M.Z.; Constantinou, C.C.
We present an Emergent Ad hoc Routing Algorithm with QoS provisioning (EARA-QoS). This ad hoc Quality-of-Service (QoS) routing algorithm is based on a swarm intelligence inspired routing infrastructure. In this algorithm, the principle of swarm intelligence is used to evolutionally maintain routing information. The biological concept of stigmergy is applied in the process of route maintenance to reduce the amount of control traffic. This algorithm adopts the cross-layer optimisation concept to use parameters from different layers to determine routing avoiding congestion areas. A lightweight QoS scheme is proposed to provide service-classified traffic control based on the data packet characteristics. The simulation results show that this novel routing algorithm performs well in a variety of network conditions.